Case report: A patient with ALK-positive large B-cell lymphoma benefited from myeloma-like treatment combined with the ALK inhibitor lorlatinib - Liu, Dan; Xing, Lijie; Wang, Hui; Li, Ping; Wei, Haichen (Frontiers in Hematology, 2024)
IntroductionAnaplastic lymphoma kinase (ALK)-positive large B-cell lymphoma (LBCL) is a rare subtype of diffuse large B-cell lymphoma (DLBCL). Patients with ALK+ LBCLs have poor response and survival outcomes when treated with traditional chemotherapy regiments. The efficacy of second- and third-generation ALK inhibitors has been reported in treating ALK+ LBCLs. Additionally, owing to the plasmablastic morphology and immune features observed in ALK+ LBCLs, plasma cell tumor therapies may be effective for this patient population. In this case report, we utilized a myeloma-like therapy combined with a third-generation ALK inhibitor for a newly diagnosed ALK+ LBCL patient.Case presentationWe reported a 32-year-old male patient diagnosed with ALK+ LBCL. Immunohistochemistry (IHC) analysis revealed a plasma cell immunophenotype characterized by CD138 positivity but negativity for mature B lymphocyte markers. The patient received six cycles of VRD (bortezomib 1.3 mg/m2 d1, 4, 8, and 11; lenalidomide 25 mg qd d1–14; dexamethasone 20 mg d1–2, d4–5, d8–9, and d11–12) and cyclophosphamide (1.0 g q3w) treatment. Lorlatinib (100 mg once daily) was added starting from the second cycle of treatment onwards. After four cycles of treatment, the patient achieved complete remission, which was maintained for more than 6 months after completing chemotherapy, without any significant safety concerns.ConclusionVRD and cyclophosphamide combined with a third-generation ALK inhibitor resulted in durable complete remission for an individual with ALK+ LBCL, suggesting it as a therapeutic option for patients with this subtype.